Proceso de atención enfermería en paciente de 28 años con Gangrena Fournier. - García Ramos, Carlos Isrrael (2023)
Fournier's gangrene can be defined as the presence of necrotizing aerobic and anaerobic polymicrobials in the genital region, affecting newborns and the elderly. Fournier suffered from underlying systemic diseases, the most common being diabetes and chronic alcoholism (Egas, 2019). The application of an algorithm of care to patients diagnosed with Fournier's gangrene reduces the risk of infection, as well as morbidity and mortality. The application of the nursing process to patients with Fournier's gangrene ensures recovery and improvement of the patient's quality of health and is recognized as a central guideline for the provision of nursing care methods using the international standard language NANDA, NOC, NIC. Successful implementation requires developing technical knowledge and interpersonal skills in addition to applying reflection on the strengths of the nursing profession.